Investigating the Role of Perceived Information Overload on COVID-19 Fear: A Moderation Role of Fake News Related to COVID-19 - Zhang, Chong; Cao, Tong; Ali, Asad (Frontiers in Psychology, 2022)
During crises, and uncertain situations such as the COVID-19 pandemic, social media plays a key function because it allows people to seek, and share news as well as personal views and ideas with each other in real-time, globally. Past research has highlighted the implications of social media during disease outbreaks; nevertheless, this study refers to the possible negative effects of social media usage by individuals in the developing Country during the COVID-19 epidemic lockdown. Specifically, this study investigates the COVID-19 fear; using survey data collected from a developing country. In total 880 entries were used to analyze the COVID-19 fear, using AMOS software. Findings indicated that information-seeking and sharing behavior of individuals on social media has a significant impact on perceived COVID-19 information overload. Perceived COVID-19 information overload has a positive impact on COVID-19 fear. In addition, fake news related to COVID-19 strengthens the relationship between perceived COVID-19 information overload and COVID-19 fear. The implication and limitations of the study are also discussed in the last section of the study.